Hardiness of parents who have mentally retarded children - Sucy, Nur Ainun; Fitriana, Dewi; Octavia, Indah Andika (Psychological Research and Intervention, 2024)
This research is motivated by the problem of hardiness in parents who have mentally retarded children. The ability of individuals to survive and adapt to stress and challenges faced. Parents who have children with mentally retarded, they are faced with various challenges when caring their children. The purpose of this study is to find out how the description of parents' hardiness and the process of stages facing the reality of having a child with a mentally reterdation and to find out the factors that influence hardiness in parents who have mentally retarded children. This study used a qualitative approach and data collection was carried out using observation and interview techniques. The primary subjects in this study are parents who have mentally retarded children, while the secondary subjects are neighbors near the subject's residence, as well as the subject's cousin. The results of the research obtained that the three subjects experienced hardiness by having mentally retarded children. This can be seen from several aspects of hardiness that exist in the subject, namely commitment, control, and challenge. The factor that influences the three subjects is coping strategy.Keywords: Hardiness, parents, mentally retarded children